Cleanskin - McDermid V. Val (Quick reads)
This is a taut psychological thriller from the bestselling author behind the popular Wire in the Blood TV series. Jack Farlowe is a career criminal, but one who has never been convicted of any offence. When his daughter dies in an arson attack, he is broken-hearted. His drowned body is washed up on a Suffolk beach, and everyone believes he has killed himself in grief. But then, one by one, Jack Farlowes enemies start to die hideous deaths!